Morphological Variation and Ecological Structure of Iroko (Milicia excelsa Welw. C.C. Berg) Populations across Different Biogeographical Zones in Benin - Christine Ouinsavi; Nestor Sokpon (International Journal of Forestry Research)
Iroko (Milicia excelsa) is a commercially important timber tree species formerly known by local people in Benin. Because of the highly attractive technological properties of its wood and its multipurpose uses, the species was subjected to intensive human pressure. Apart from strong climate oscillation during the Pleistocene, human caused habitat fragmentation through continuous land clearing for agriculture, extensive forests exploitation and urbanization induced the occurrence of many isolated forest plots and trees species among which Milicia excelsa trees. As fragmentation was proved to have deleterious effects on genetic diversity within a species and its morphological structure, it was of interest to investigate the current demographic, morphological and genetic structure of M. excelsa before coming up with conservation strategies. In the current study, morphological variation and ecological structure of M. excelsa populations were assessed in Benin using transect sampling method and multivariate analyses including principal component, cluster and canonical discriminant analyses. On the basis of morphological parameters, M. excelsa individuals and populations were clustered into four and discrimination of groups indicated that most of variations were highly related to edaphic factors and annual rainfall. Erratic diameter distribution was found for many populations although most of them showed bell shaped diameter distribution.